Strong Family Ties: The Key to Preventing Anti-Social Behavior in Society: Hubungan Keluarga yang Kuat: Kunci untuk Mencegah Perilaku Anti-Sosial dalam Masyarakat - Dushanov Rustam Khujanovich; Alibekov Botir Sultanbekovich (Universitas Muhammadiyah Sidoarjo, 2023)
This article aims to analyze the consequences of negative family environments, such as divorce, shortcomings in child-rearing, and various disputes and conflicts. Using qualitative analysis, the author emphasizes the importance of educating the mature generation on the psychological factors of mutual understanding, emotional closeness, and respect within the family. By promoting moral and ethical values from a young age, families can prevent the formation of anti-social behavior and maintain positive social relations between family members. The study suggests that parents should focus on developing the correct perception and mechanisms of family relationships to maintain emotional and spiritual closeness and prevent tensions. The implications of this research are particularly relevant to policymakers, educators, and parents seeking to create strong family ties and reduce negative effects on society. Highlights: Unhealthy family environments can lead to negative consequences such as anti-social behavior. Parents should focus on developing mutual understanding, emotional closeness, and respect within the family to prevent negative effects. Promoting moral values from a young age can help create strong family ties and prevent the formation of anti-social behavior. Keywords: family relationships, anti-social behavior, psychological factors, moral values, emotional closeness.